Bioaccumulation of metals in mangrove snail (Cerithidea obtusa) from Southwest Johor, Malaysia - Krishnan, Kumar; Saion, Elias; Yap, Chee Kong; A.S., Nadia (Horizon Research Publishing, 2023)
Pollutants are persistent in the environment, taint the food chain, and harm people's health because of their toxicity. In this study, mangrove snails called Cerithidea obtusa (C. Obtusa) were gathered from Southwest Johor, Malaysia, and the amounts of macro and micro elements Ca, Fe, K, Mg, Na, As, Mn, and Zn in their soft tissues, shells, and related surface sediments were analysed. The Neutron Activation Analysis (NAA) method was used to calculate the elements concentration. The mean concentrations of Ca, Fe, K, Mg, Mn, Na, As, Mn and Zn were found to be followed by the order Fe > Na > K > Mg > Ca > Na > Mn > Zn > As in the sediment, while Ca > Na > K > Mg > Fe > Zn > Mn > As and Ca > K > Na > Mg > Fe > Mn > Zn > As in the soft tissue and shell of C. Obtusa respectively. The Enrichment Factor (EF) of Ca, K, Mg, Na, As, Zn, and Mn ranged from 0.58 to 2.58, 0.82 to 1.04, 1.14 to 2.34, 2.32 to 4.18, 1.31 to 3.45, 1.11 to 1.52, and 0.23 to 0.38, respectively. Mn had the lowest EF (0.23), and 4.18 had the greatest (Na). Most of the elements showed geoaccumulation index (Igeo) < 0 except for As and Na. Based on the Biota-Sediment Accumulation Factor (BSAF), the shell of C. Obtusa acts as a deconcentrator for all the elements except for Ca.